Afraid of the Dark? The Influence of Natural and Artificial Light at Night on the Behavioral Activity of a Nocturnal Gecko - Nordberg, Eric J.; Schwarzkopf, Lin (Frontiers in Ecology and Evolution, 2022)
Both natural and artificial light at night can strongly influence animal behaviour. Nocturnal animals often alter activity dependent on lunar light levels, to increase prey capture, minimise detection by predators, or both. Trade-offs among these ecological effects are likely to have a strong influence on behaviour and fitness. Here, we examined the influence of light at night on nocturnal geckos that are both predators and prey, and use both natural and anthropogenic habitats. We tested the influence of illumination on the relative abundance and behavioural activity of native geckos in natural woodlands and under laboratory conditions. We hypothesised that Australian native house geckos (Gehyra dubia) would avoid activity on nights with high moon brightness, to minimise exposure to predators, consistent with the predation risk hypothesis. Counter to our prediction, we found a positive relationship between house gecko activity and moon brightness, i.e., house geckos were more active on bright nights. This behaviour may allow house geckos to better see their prey while also increasing the visibility of approaching predators. In the laboratory, house geckos had shorter latency times to emerge from a shelter under low light conditions compared to darkness equivalent to a new moon, a trend consistent with higher activity under brighter conditions in the field. Light at night, from both natural and artificial sources, clearly influences the behaviour and activity of geckos, but perhaps not in the ways we expect. Reducing the risk of attack from predators in darkness, and increasing prey capture success using vision, may increase the benefits of activity in lit conditions, compared to total darkness.